Blood shortages and changes to massive transfusion protocols: Survey of hospital practices during the COVID-19 pandemic. (February 2022) - Jacobs, Jeremy W.; Booth, Garrett S.
Abstract: Introduction: The COVID-19 pandemic has resulted in severe ongoing blood shortages across the US, despite employment of numerous blood-conservation measures. Massive transfusion protocols (MTP) are one resource-intensive practice that utilize significant amounts of blood products. Alterations to the composition of MTP parameters to conserve scarce biologic resources have hitherto not been examined during the pandemic. Methods: An anonymous 18-question survey was administered to 115 hospitals with valid email contact information. Survey questions addressed whether institutions have altered their MTPs due to the COVID-19 pandemic and blood shortages, and if so, what adjustments they have made. Additional details concerning potential differences in the number and cycles of MTPs and blood product wastage during the COVID-19 pandemic compared to the year prior were assessed. Results: 50 responses were received (43 % response rate). 10 % (5/50) of institutions altered their MTPs utilizing a variety of approaches in attempt to conserve blood during the COVID-19 pandemic. Four additional institutions intend to alter them if it becomes necessary. Following onset of the COVID-19 pandemic, 24 % of institutions (12/50) reported an increase in monthly MTP activations, while 16 % (8/50) reported decreased activations compared to prior to the pandemic. 22 % (11/50) of institutions experienced increased blood wastage, whereas 16 % (8/50) reported decreased waste compared to pre-pandemic. Discussion: The results of this survey highlight a variety of mechanisms by which institutions have attempted to conserve blood via altering MTPs. Whether an institution adjusted their MTP does not correlate with changes in blood product wastage compared to pre-pandemic.